Prognostic significance of myocardial performance index in patients with ischemic heart disease - Haytham Soliman; Ayman Fathy Kaddah; Azza Farrag; Waleed Ammar (Cairo : Haytham Soliman, 2010)
Estimation of myocardial performance is always a field for enova tion accurate estimation of ventricular contractile functions of utmost importance in deciding the whole management and detecting prognosis
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Cardiology
Issued also as CD
Keywords: Echocardiographic changes in myocardial infarction; Role of echocardiography in myocardial infarction; Tissue doppler imaging (TDI)